Species turnover and vertical partitioning of ant assemblages in the Brazilian Amazon: A comparison of forests and savannas - Vasconcelos, Heraldo L.; Vilhena, José M.S. (Biotropica, 2006)
We measured beta diversity, or turnover in species composition, of ant assemblages inhabiting patches of forest and savanna (cerrado) near Alter do Chão, in the Brazilian Amazon. In addition, we assessed vertical partitioning of these assemblages by comparing the ground and lower vegetation strata within each habitat. Ants attracted to sardine baits were collected along transects in 39 savanna and 34 forest sites scattered over a 16 km × 16 km landscape. There were about twice as many species in the forest as in the savanna, and within both habitats, we collected more species on the ground than in the vegetation. Similar results were obtained when analyzing data at the level of individual transects, indicating that ant species richness is affected by both habitat and strata. About two-thirds of the species recorded in the savanna were also found in the forest. Within both habitats, a large proportion of the species found in the least species-rich stratum (vegetation) were also found in the richer one (ground). However, ordination analysis, using data from individual transects, revealed that different habitats and strata can be clearly discriminated from each other in terms of their ant species composition. Each habitat and stratum had a number of characteristic (indicator) species which, although generally not exclusive to that particular habitat and stratum, predominated there. Our findings indicate that habitat and strata specialization is an important factor governing the organization of ant communities in Amazonia. © 2005 The Author(s).
Keywords: Ant; Coexistence; Community Structure; Niche Partitioning; Savanna; Species Diversity; Tropical Forest; Turnover; Vertical Distribution; Alter Do Chao; Brasil; Para [brazil]; South America; Formicidae